Assessment of platelet indices and their interpretation in thrombocytopenia - Kaur, Kanwaljeet (International Journal of Psychosocial Rehabilitation, 2008)
condition in hospitalized patients, may go unnoticed. The present study was conducted to assess platelet indices and their interpretation in thrombocytopenia. Materials & Methods: 58 patients of thrombocytopenia of both genders were put in group I and controls in group II. Group I was further divided into group A – as accelerated destruction and b- as impaired production. The laboratory used a 5-part automated hematology analyzer to process all patient blood samples that were received in K3-EDTA anticoagulated vacutainers within an hour of collection. (Horiba Medical, Pentra ES 60) Platelet count and platelet parameters, such as mean platelet volume (MPV), platelet distribution width (PDW), platelet large cell ratio (P-LCR), and platelet crit (PCT), were recorded from the analyzer-generated reports. Results: Group I had 38 males and 20 females and group II had 29 each male and female. In group A, B and II, mean platelets count (x 109/L) was 106.2, 75.2 and 254.8, PDW (fL) was 19.5, 17.1 and 16.3, MPV (fL) was 13.7, 13.2 and 12.3, P- LCR (%) was 54.2, 42.7 and 40.9 and PCT (%) was 0.09, 0.03 and 0.21 respectively. The difference was significant (P<0.05). Conclusion: PCT and platelet count are directly correlated, and platelet crit can be used to evaluate both quantitative and qualitative platelet problems. The mechanism underlying the low platelet count can be deciphered using additional parameters such as PDW, PLCR, and MPV in addition to PCT. High index values suggest a greater breakdown of platelets in the bloodstream, while low values may be the result of impaired production brought on by primary or secondary bone marrow disease.